SPDA modified MIL-101 modified polyether sulfone ultrafiltration membrane as well as preparation method and application thereof
By modifying MIL-101 nanoparticles with sulfonated dopamine and adding it to the ultrafiltration membrane, the problems of low organic matter rejection rate and serious membrane fouling of the ultrafiltration membrane in high-algae water treatment were solved, and the water flux and UV254 rejection rate were improved. and anti-pollution effects.
Patent Information
- Application Number
- CN202411815335.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-11
AI Technical Summary
In the treatment of high algae water, the existing ultrafiltration membranes have problems with low organic matter retention and serious membrane contamination, making it difficult to effectively remove extracellular organic matter from algae cells.
MIL-101 nanoparticles were modified with sulfonated dopamine through the Michael addition reaction to prepare SPDA-modified MIL-101 nanomaterials, and added to the polyethersulfone ultrafiltration membrane through the blending modification method to improve the hydrophilicity and resistance of the membrane. pollution performance.
It significantly improves the water flux, UV254 rejection rate and anti-pollution ability of the ultrafiltration membrane, improves the pore structure and hydrophilicity of the membrane, and enhances the filtration performance of extracellular organic matter in algae cells.
Smart Images

Figure CN119345906A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ultrafiltration membranes, and in particular to an SPDA-modified MIL-101-modified polyethersulfone ultrafiltration membrane and a preparation method and application thereof. Background Art
[0002] In recent years, with the high frequency of algal blooms in surface water, it has posed a huge challenge to drinking water safety. Suspended pollutants in high-algae water bodies, algal cells and their secreted extracellular organic matter (EOM), especially the characteristics of EOM such as easy solubility, easy dispersion, and complex composition, are the main reasons for the deterioration of effluent quality, affecting the operation effect of conventional water treatment processes. Ultrafiltration has been proven to be an efficient, reliable, and feasible technology for treating high-algae water. Ultrafiltration technology can maintain the integrity of algal cells and avoid the problem of algal cell breakage, but there are still problems such as low organic matter retention rate and severe membrane pollution in high-algae water bodies.
[0003] Studies have shown that hydrophilic modification of ultrafiltration membranes can effectively alleviate ultrafiltration membrane fouling. Usually, mixed matrix membranes are prepared by methods such as hydrophilic polymer blending, hydrophilic monomer grafting, coating, and blending of hydrophilic nanoparticles. Among them, metal organic frameworks (MOFs) have great advantages such as large specific surface area, adjustable structure, and easy functionalization, which can effectively improve the hydrophilicity and filtration capacity of ultrafiltration membranes. In the prior art, Wang et al. modified the ultrafiltration membrane by blending UIO-66, which improved the humic acid removal rate and alleviated the membrane fouling of the ultrafiltration membrane. Muayad et al. modified the ultrafiltration membrane by adding metal organic frameworks (UIO-66 and UIO-66-NH 2 ) greatly improves the pure water flux and flux recovery rate of the membrane, showing an enhanced anti-pollution effect. In addition, due to the poor compatibility of nanoparticles with the membrane matrix, they are prone to agglomeration. Scholars often modify nanoparticles to prepare mixed matrix membranes with better performance. For example, nanoparticles are modified by tannic acid, polydopamine, etc. to improve compatibility with the membrane matrix.
[0004] There are few reports on the preparation of mixed matrix membranes by modifying nanoparticles with sulfonated polydopamine. Summary of the invention
[0005] The present invention is based on the Michael addition reaction, and the MIL-101 nanoparticles are modified with sulfonated dopamine, and a hydrophilic polyethersulfone (PES) membrane is prepared by a blending modification method. First, SPDA-modified MIL-101 nanomaterials are synthesized, and the PES ultrafiltration membrane is modified by blending, and is used to improve the filtration performance and anti-pollution performance of extracellular organic matter (EOM) of algae cells. The effects of SPDA-modified MIL-101 nanomaterials on the performance structure of ultrafiltration membranes at different addition amounts are further analyzed. The permeability and separation performance of the membrane are evaluated by pure water flux and pollution flux. The anti-pollution performance of the membrane is evaluated by alternating filtration of EOM solution and pure water for three cycles, the proportion of reversible pollution and irreversible pollution and the flux recovery rate.
[0006] The first aspect of the present invention provides a method for preparing a SPDA-modified MIL-101 modified polyethersulfone ultrafiltration membrane, comprising the following steps:
[0007] S1. Preparation of MIL-101: CrCl 3 6H 2 The O aqueous solution and the PTA aqueous solution were stirred, heated for reaction, cooled to room temperature, centrifuged, and the precipitate was collected, washed and dried to obtain MIL-101;
[0008] S2. Preparation of SPDA-modified MIL-101: MIL-101 was dispersed in the mixed solution, ultrasonicated to form a suspension, dopamine hydrochloride was added to the suspension, stirred, injected with Tris-HCl buffer, stirred for 12-24 hours, and then sodium 3-mercapto-1-propane sulfonate was added to continue the reaction for 10-30 hours, washed and centrifuged, and vacuum dried to obtain SPDA-modified MIL-101;
[0009] S3. Preparation of SPDA-modified MIL-101 modified polyethersulfone ultrafiltration membrane: PVP and SPDA-modified MIL-101 were dissolved in NMP, and after ultrasonic dispersion, dry PES was added and stirred for 10-30 hours. The mixture was allowed to stand for degassing, and the membrane was scraped on a glass plate with a scraper to obtain SPDA-modified MIL-101 modified polyethersulfone ultrafiltration membrane.
[0010] As a preferred embodiment, the CrCl 3 6H 2 The mass ratio of O and PTA is (2-3):(1-2).
[0011] As a preferred embodiment, the heating reaction is carried out at 200-220° C. for 10-15 hours.
[0012] As a preferred embodiment, the mass ratio of MIL-101 to dopamine hydrochloride is (0.05-1): (0.05-1).
[0013] As a preferred embodiment, the mixed liquid is a mixed liquid of deionized water and anhydrous ethanol, and the mass ratio of deionized water to anhydrous ethanol is (1-2): (1-2).
[0014] As a preferred embodiment, the mass ratio of the SPDA-modified MIL-101, PVP and PES is (0.05-0.2):1:16.
[0015] The second aspect of the present invention provides a SPDA-modified MIL-101-modified polyethersulfone ultrafiltration membrane obtained by the above-mentioned preparation method.
[0016] The third aspect of the present invention provides an application of a SPDA-modified MIL-101 modified polyethersulfone ultrafiltration membrane in sewage treatment.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The present invention uses MIL-101 as a raw material, synthesizes SPDA-modified MIL-101 nanomaterials by adhesion modification of sulfonated polydopamine, adds SPDA-modified MIL-101 into PES casting solution by a blending modification method, and prepares a modified ultrafiltration membrane by non-solvent-induced phase separation.
[0019] 2. The present invention modifies the surface of MIL-101 with sulfonated polydopamine and successfully prepares SPDA-modified MIL-101 nanomaterials. The material not only has the structural characteristics of MIL-101, but also has the hydrophilicity and electronegativity of sulfonated polydopamine, which provides a basis for the subsequent preparation of ultrafiltration membranes.
[0020] 3. Through the study of water contact angle, membrane surface electronegativity, irreversible contamination degree, etc., it is proved that the addition of SPDA-modified MIL-101 improves the membrane pore structure of the ultrafiltration membrane, increases the hydrophilicity and electronegativity, and thus increases the water flux of the ultrafiltration membrane. 254 Retention rate and anti-pollution ability.
[0021] 4. By comparing the modified membranes, the ultrafiltration membrane with 0.1wt% SPDA modified MIL-101 has the best comprehensive performance, with a membrane water contact angle of 54.89° and a water flux of 540L / (m 2 h), UV 254 The rejection rate increased by 16%, and the flux recovery rate after three cycles reached 89%, providing a solid foundation for the application of ultrafiltration in high-algae water. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The microstructure and elemental surface distribution spectrum of MIL-101 and SPDA modified MIL-101, Figure 1(a) is MIL-101, Figure 1 (b) SPDA-modified MIL-101.
[0023] Figure 2 This is the elemental composition diagram of SPDA modified MIL-101.
[0024] Figure 3 XPS and FTIR spectra of MIL-101 and SPDA modified MIL-101.
[0025] Figure 4 This is the surface morphology and structure analysis diagram of the ultrafiltration membrane at different addition amounts of SPDA-modified MIL-101.
[0026] Figure 5 This is the water contact angle and Zeta potential diagram of ultrafiltration membrane.
[0027] Figure 6 This is a graph showing ultrafiltration membrane flux versus UV254 rejection rate.
[0028] Figure 7 This is the ultrafiltration membrane flow diagram and contamination degree diagram.
[0029] Figure 8 The absorbance diagram of EOM solution and permeate measured by UV-visible spectrophotometer. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Polyethersulfone PES (Mn = 100000) was purchased from BASF AG, Germany, analytical grade;
[0032] N-Methylpyrrolidone (NMP) was provided by Aladdin and was analytically pure;
[0033] Polyvinylpyrrolidone (PVP) K30 was purchased from Tianjin Zhonglian Chemical Reagent Co., Ltd., analytical grade;
[0034] Dopamine hydrochloride (PDA) was purchased from Shanghai McLean Reagent with a purity of 98%;
[0035] Tris-HCl buffer was purchased from Xiamen Aimimanni Biotechnology Co., Ltd., analytical grade;
[0036] Chromium chloride hexahydrate (CrCl3·6H2O) was purchased from Shanghai Aladdin Reagent with a purity of 98%;
[0037] Terephthalic acid (PTA) was purchased from Shanghai Aladdin Reagent with a purity of 99%;
[0038] Sodium 3-mercapto-1-propane sulfonate was purchased from Shanghai Aladdin Reagent with a purity of 98%.
[0039] Example 1
[0040] This embodiment provides a SPDA-modified MIL-101 modified polyethersulfone ultrafiltration membrane, and the preparation method comprises the following steps:
[0041] S1. Preparation of MIL-101: 2.66 g CrCl 3 6H 2 O was dissolved in 45 mL of deionized water, 1.66 g of PTA was dissolved in 45 mL of deionized water, the two solutions were mixed and stirred, placed in an oven at 210 ° C for 12 hours, cooled to room temperature, centrifuged, and the precipitate was collected, washed alternately with deionized water and ethanol to remove impurities, and then dried to obtain MIL-101;
[0042] S2. Preparation of SPDA-modified MIL-101: 0.1 g of MIL-101 was dispersed in 60 mL of a mixed solution (V(deionized water) ∶ V(ethanol)=1∶1), and ultrasonicated for 10 min to form a suspension. 0.1 g of dopamine hydrochloride was added to the suspension, stirred, and 20 mL of Tris-HCl buffer was injected. After stirring for 12 h, 0.1 g of sodium 3-mercapto-1-propane sulfonate was added and the reaction was continued for 12 h. The mixture was washed and centrifuged, and then vacuum dried to obtain SPDA-modified MIL-101.
[0043] S3. Preparation of SPDA-modified MIL-101 modified polyethersulfone ultrafiltration membrane: According to the mass percentage, 1% PVP and 0.1% SPDA-modified MIL-101 were dissolved in 82.95% NMP, and after ultrasonic dispersion, 16% dry PES was added and stirred for 12 hours. The mixture was allowed to stand for degassing, and a 150 μm scraper was used to scrape the membrane on a glass plate to obtain the SPDA-modified MIL-101 modified polyethersulfone ultrafiltration membrane. The membrane was stored in deionized water, and the water was changed every 12 hours.
[0044] Example 2
[0045] This embodiment provides a SPDA-modified MIL-101-modified polyethersulfone ultrafiltration membrane. The specific implementation is the same as that of Example 1, except that 0% SPDA is added to S3 to modify MIL-101.
[0046] Example 3
[0047] This embodiment provides a SPDA-modified MIL-101-modified polyethersulfone ultrafiltration membrane. The specific implementation is the same as that of Example 1, except that 0.05% SPDA is added to S3 to modify MIL-101.
[0048] Example 4
[0049] This embodiment provides a SPDA-modified MIL-101-modified polyethersulfone ultrafiltration membrane. The specific implementation is the same as that of Example 1, except that 0.15% SPDA is added to S3 to modify MIL-101.
[0050] Example 5
[0051] This embodiment provides a SPDA-modified MIL-101-modified polyethersulfone ultrafiltration membrane. The specific implementation is the same as that of Example 1, except that 0.2% SPDA is added to S3 to modify MIL-101.
[0052] Performance Testing
[0053] The following tests were performed on the MIL-101, SPDA-modified MIL-101 (hereinafter referred to as modified nanoparticles), and SPDA-modified MIL-101-modified polyethersulfone ultrafiltration membrane (hereinafter referred to as ultrafiltration membrane) prepared in the above examples:
[0054] (I) Structure and performance characterization
[0055] ① The microstructure and element surface distribution spectrum of the modified nanoparticles were analyzed by SEM. Figure 1 . Figure 1 (a) It can be observed that MIL-101 exhibits an octahedral morphology with a particle size between 200 nm and 300 nm, which is a typical feature of MIL-101 crystals. Figure 1 (b) SPDA-modified MIL-101 exhibits a similar octahedral morphology with little change in particle size, but the lattice plane is slightly rough, and is a structure wrapped in a polydopamine shell.
[0056] ② Use XPS to analyze the elemental composition of the modified nanoparticles. The results are shown in Figure 2 As can be seen from the figure, MIL-101 contains Cr, O, and C elements, and N and S elements appear in dopamine after oxidation self-healing, which further indicates that the sulfonated polydopamine coating is successfully coated on MIL-101. Figure 3 (a) The N1s and S2P characteristic peaks appearing in the XPS graph also indicate the successful loading of the sulfonic acid group.
[0057] ③ Use FTIR to analyze the functional group composition of modified nanoparticles, with a scanning range of 4000-500 cm -1 The results are shown in Figure 3 From the FTIR spectrum Figure 3 (b) It can be seen that 1018 and 748 cm -1 The characteristic peak appears due to the vibration of the benzene ring inside the nanoparticles. -1 The peak at 1168cm is the characteristic peak of Cr-O stretching vibration. -1 The characteristic peak at 3400cm is caused by the vibration of the sulfonic acid group. -1 The broad absorption peak is caused by the vibration of -OH or -NH functional groups in dopamine. The above results show that the modification of sulfonated polydopamine nanoparticles (SPDA modified MIL-101) is successful.
[0058] ④Ultrasonic membrane microstructure morphology was analyzed by SEM; the surface roughness of the ultrafiltration membrane was analyzed by AFM. Figure 4 . When added in small amounts, such as M1 (Example 3) and M2 (Example 1), the membrane surfaces show a smooth and flat morphology; with the further addition of nanoparticles, segregated nanoparticles gradually appear on the surfaces of M3 (Example 4) and M4 (Example 5). At an addition amount of 0.1wt%, as shown in M2 (Example 1), the nanoparticles are evenly dispersed and the surface is smooth and flat. This is because polydopamine increases the compatibility between the membrane matrix and the nanoparticles. However, when the addition amount is greater than 0.1wt%, the nanoparticles agglomerate on the surface and the surface is noticeably rough. The membrane surface roughness AFM is as follows Figure 4 As shown in the figure, the surface roughness of the membrane shows a trend of first decreasing and then increasing. The high hydrophilicity of the nanoparticles leads to the acceleration of the phase separation process, resulting in a smoother surface. The subsequent increase in roughness is because the nanoparticles increase the viscosity of the casting liquid, delay the phase separation process, and cause the aggregation of nanoparticles, resulting in greater roughness.
[0059] ⑤ Analysis of the membrane pore structure of all membranes Figure 4 As shown in the cross-sectional SEM. As can be seen from the figure, all ultrafiltration membranes are composed of three parts: bottom voids, middle finger-like holes and a dense sponge-like pore structure at the top of the membrane. From M0 (Example 2) to M2 (Example 1), with the addition of nanoparticles, the pore structure changes from an inclined state to a straight state, and the straight pore structure is more conducive to the passage of water molecules, thereby improving the water permeability of the ultrafiltration membrane. From M2 (Example 1) to M4 (Example 5), with the continued addition of nanoparticles, the pore structure continues to change to an inclined state, and the voids in the bottom layer of the ultrafiltration membrane are all improved. This enhanced structure can improve the mechanical properties of the ultrafiltration membrane and is more conducive to practical applications.
[0060] ⑥ Use the contact angle / surface tension meter to analyze the water contact angle of the ultrafiltration membrane; use the solid surface Zeta potential tester to analyze the surface Zeta potential of the ultrafiltration membrane. The water contact angle and Zeta potential diagram are as follows Figure 5Generally speaking, membrane surface hydrophilicity is an important indicator for evaluating membrane performance, and it plays a vital role in improving permeability and anti-fouling performance. Figure 5 The water contact angle of the M0 (Example 2) membrane shown in (a) is 71°. After adding different amounts of SPDA to modify MIL-101, the membrane contact angle shows a trend of first decreasing and then increasing, among which the M2 (Example 1) membrane has the lowest contact angle of 54.89°. Since the MIL-101 modified with sulfonated polydopamine has good hydrophilicity, the addition of nanoparticles can improve the hydrophilicity of the membrane surface.
[0061] Since most pollutants carry negative charges, increasing the electronegativity of the membrane surface can enhance the charge repulsion between pollutants and the membrane surface, thereby improving the membrane's anti-pollution ability. Figure 5 (b) The membrane surface has a negative charge at pH = 7. This is because the number of hydroxyl and sulfonic acid groups in the modified nanoparticles increases, which increases the electronegativity of the membrane surface. As the pH increases from 5 to 9, the Zeta potential of the original membrane decreases from -19mV to -41mV, while the M2 (Example 1) membrane decreases from -21mV to -60mV. Compared with the unmodified membrane, the electronegativity of the Zeta potential of the modified membrane increases by 1.77 times. This is related to the abundant hydroxyl and sulfonic acid groups provided by sulfonated polydopamine. The increased electronegativity can better repel negatively charged pollutants and provide better anti-pollution ability.
[0062] ⑦Use UV-visible spectrophotometer to measure the absorbance of EOM solution and permeate. Figure 8 .
[0063] (II) Porosity and pore size analysis of ultrafiltration membrane
[0064] The porosity and average pore size of the ultrafiltration membrane were measured by wet-dry weight method. The wet membrane was the ultrafiltration membrane prepared in Example S3 and stored in water, and the dry membrane was the wet membrane dried to a constant weight.
[0065] Wet film (4cm 2 ) was first weighed and then dried at 100°C for 12 hours. The porosity (ε) was calculated as:
[0066]
[0067] Where W 1 and W 2 are the weights of wet and dry films (g), ρ is the density of water (g / cm 3 ), A is the membrane area (cm 2 ), l (cm) is the thickness of the film.
[0068] The average pore size r of the membrane was calculated by the Guerout-Elford-Ferry equation (2).
[0069]
[0070] Where η is the viscosity of water (pa·s), Q is the volume of permeated water (m 3 / s), ΔP is the working pressure (Pa).
[0071] The results are shown in Table 1.
[0072] Table 1
[0073]
[0074] (III) Pure water flux and UV of ultrafiltration membrane 254 Retention rate test
[0075] The pure water flux test uses Shanghai Mosu ultrafiltration cup for dead-end filtration. First, the membrane sample is pre-pressed at 0.15MPa for 30min. After the test system is stable, the pure water flux is measured at 0.1MPa and calculated using formula (3):
[0076]
[0077] Where: J W is the pure water flux, L / (m 2 ·h); V is the volume of the filtrate during the measurement time, L; A is the effective filtration area of the ultrafiltration membrane, m 2 ; t is the ultrafiltration membrane filtration time, h.
[0078] EOM solution retention rate test: The laboratory cultured Microcystis aeruginosa solution was used as a simulated natural water body, and the EOM solution was extracted by high-speed centrifugation. 254 =0.030~0.035; DOC=5.0mg / L. Use UV-visible spectrophotometer at wavelength 254nm to measure the absorbance of the permeate, and obtain the concentration of the permeate and the original solution through the standard curve. Calculate UV by formula (4) 254 Retention rate.
[0079]
[0080] Test results such as Figure 6 As shown in Figure 2, with the addition of nanoparticles, the pure water flux of the modified membrane, the EOM solution contamination flux and the UV 254 The water flux of M2 (Example 1) reached 540L / (m 2 ·h), equivalent to the original membrane 287L / (m 2·h) is 1.88 times. The water flux of ultrafiltration membrane is often affected by many factors. The M2 (Example 1) membrane has a straight pore structure, increased porosity, increased hydrophilicity, etc. In addition, metal organic frameworks are porous materials, and MIL-101 has Pore size, much larger than the diameter of a water molecule This structure is conducive to the transport of water molecules. The reduction in pure water flux of M3 (Example 4) and M4 (Example 5) can be attributed to the reduction in porosity and hydrophilicity.
[0081] UV of M0 (Example 2) film 254 The interception rate is only 14%, while the modified membrane M2 (Example 1) can reach up to 30%. There are a lot of small molecular organic matter in the algae-derived pollutants, which can easily pass through the membrane, resulting in the unmodified PES membrane being sensitive to UV 254 The size repulsion effect is poor. Both the extracellular organic matter and the surface of the nanocomposite membrane are negatively charged. Compared with the pure PES membrane, the nanocomposite membrane has a stronger charge repulsion between the extracellular organic matter and the membrane surface. Figure 5 (b), thereby enhancing the repulsion of extracellular organic matter and thus improving the effluent quality.
[0082] (IV) Anti-pollution performance test
[0083] In order to test the anti-pollution performance of the modified ultrafiltration membrane, deionized water and EOM contaminated solution were alternately used for dead-end filtration. 200 mL of pure water was first filtered at 0.1 MPa, and then the solution was replaced with 300 mL of EOM contaminated solution. The flux change was recorded by an electronic balance; 200 mL of deionized water was used for in-situ backwashing; the solution was converted to pure water again, and the filtration was repeated three times in this way. The flux recovery rate (FRR) after three cycles of the membrane was calculated.
[0084] R ir , R r , R t They are irreversible pollution, reversible pollution and total pollution, calculated according to formulas (5) to (8):
[0085]
[0086] R r =(R t -R ir )×100% (8)
[0087] Where: J e3 Terminal flux at the end of the third cycle; J s4 Initial flux of the 4th cycle; J 0 Initial flux of ultrafiltration membrane.
[0088] In order to evaluate the anti-fouling performance of the membrane, the flux changes of EOM contaminated solution and pure water filtered by the modified membrane were investigated for three filtration cycles. Figure 7 shown. Figure 7 (a) is the test result of five membrane circulation filtration. Due to the interaction between the secretions of algae cells and the membrane surface during the filtration process, the flux of EOM solution is lower than that of pure water, and it shows a gradually decreasing trend, indicating that small molecular pollutants in the EOM solution will gradually block the membrane pores, and large molecular pollutants will gradually form a filter cake layer, resulting in a decrease in membrane flux. Due to the increased hydrophilicity and electronegativity, the water flux recovery rate of the modified membrane is as follows Figure 7 (b), which is better than the 72% flux recovery rate of the unmodified M0 (Example 2). The flux recovery rate of M2 (Example 1) reached 89% after three cycles. The flux recovery rate trend also showed a trend of first increasing and then decreasing. The flux recovery rate change trend was consistent with the membrane hydrophilicity trend. The proportion of irreversible contamination of the modified membrane was Figure 7 (b), wherein the irreversible contamination Rir of the modified membranes was significantly reduced after three cycles, the irreversible contamination of M0 (Example 2) was 28%, and the irreversible contamination of M2 (Example 1) was 11%, and the irreversible contamination was reduced by 17%. The effective mitigation of the modified membranes is mainly attributed to the increase in the hydrophilicity and electronegativity of the membranes. The hydration layer formed on the membrane surface reduces the contamination layer formed by the contact between the pollutants and the membrane. The negative charge on the membrane surface increases the repulsion between the pollutants and the membrane surface, and improves the anti-pollution ability of the membrane. Among them, the SPDA-modified MIL has the best anti-pollution effect at 0.1wt% addition, and its flux recovery rate is 89%.
[0089] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a SPDA-modified MIL-101 modified polyethersulfone ultrafiltration membrane, characterized in that: The steps include: S1. Preparation of MIL-101: Stirring CrCl3·6H2O aqueous solution and PTA aqueous solution, heating the reaction, cooling to room temperature, centrifuging, collecting the precipitate, washing and drying to obtain MIL-101; S2. Preparation of SPDA-modified MIL-101: MIL-101 was dispersed in the mixed solution, ultrasonicated to form a suspension, dopamine hydrochloride was added to the suspension, stirred, injected with Tris-HCl buffer, stirred for 12-24 hours, and then sodium 3-mercapto-1-propane sulfonate was added to continue the reaction for 10-30 hours, washed and centrifuged, and vacuum dried to obtain SPDA-modified MIL-101; S3. Preparation of SPDA-modified MIL-101 modified polyethersulfone ultrafiltration membrane: PVP and SPDA-modified MIL-101 were dissolved in NMP, and after ultrasonic dispersion, dry PES was added and stirred for 10-30 hours. The mixture was allowed to stand for degassing, and the membrane was scraped on a glass plate with a scraper to obtain SPDA-modified MIL-101 modified polyethersulfone ultrafiltration membrane.
2. The preparation method according to claim 1, characterized in that: The mass ratio of CrCl3·6H2O to PTA is (2-3):(1-2).
3. The preparation method according to claim 2, characterized in that: The heating reaction is carried out at 200-220° C. for 10-15 hours.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the MIL-101 to dopamine hydrochloride is (0.05-1):(0.05-1).
5. The preparation method according to claim 4, characterized in that: The mixed liquid is a mixed liquid of deionized water and anhydrous ethanol, and the mass ratio of deionized water to anhydrous ethanol is (1-2): (1-2).
6. The preparation method according to claim 5, characterized in that: The mass ratio of the SPDA-modified MIL-101, PVP and PES is (0.05-0.2):1:
16.
7. A SPDA-modified MIL-101 modified polyethersulfone ultrafiltration membrane, characterized in that: Obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the SPDA-modified MIL-101 modified polyethersulfone ultrafiltration membrane according to claim 7 in sewage treatment.
Citation Information
Patent Citations
Metal-organic framework MIL-160 film, preparation method and application
CN108889132A
Sulfonated porous polymer nanoparticle-metal organic framework composite cation exchange membrane and preparation method thereof
CN115888400A
Preparation method of proton exchange membrane
CN118693317A
PDA-coated MIL-101 functionalized ultrafiltration membrane and application thereof in treatment of algae-laden water
CN118751065A
Sulfonated poly(aryl ether) membrane including blend with phenol compound
US20120225960A1
Cited By
Preparation method and application of titanium-oxygen cluster compound composite ultrafiltration membrane
CN122098305A